Implementasi Panggung TV Sekolah Sebagai Media Informasi di TK Islam Rahmaniyah Kota Balikpapan - Rika Amelia; Sri Watini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Information is important for the update, so that information will be conveyed to the user effectively and efficiently, and the media must be the latest developments, therefore, a digital platform was created by the nation's children, namely school television. Where this school's TV can be accessed easily by anyone, anywhere, anytime. The study is intended to describe the application of the school features of TV as school media. The study uses qualitative descriptive methods. Data mining uses interviews and documentaries. The observed components include school TV use and the benefits of school stage features. The result of this study is that school TV is very useful as information media to parents/guardians given intratubular and extracurricular children, especially in the Rahmaniyah Islamic Kindergarten in Balikpapan. School TV makes it possible for teachers to increase their creativity in planning, organizing, and realizing the form of the programming of children's activities on the stage of school TV. This can be used as information media to facilitate parents’ access to school TV channels, especially children's activities in kindergarten.